Uriel Orlow : Unmade Film : The Reconnaissance. (Zürich : Edition Fink, Contemporary Art Publishers, 2014)
Unmade Film: The Reconnaissance presents extracts from a fictional conversation about a possible future film between Pier Paolo Pasolini, Robert Smithson (spoken by three voices), overheard sometime between 1963 and 1967, somewhere between Palestine and New Jersey. The backdrop of the conversation consists of ‘pastoral’ scenes of ruins in Palestine: Lifta, the only remaining ruin of more than 400 villages that were depopulated in 1948 and a new, unfinished construction near Ramallah. Voices: Valérie de Dietrich, Vincent Ozanon, Jérôme Robart Translation: Rula Giacaman (Arabic), Daniela Almansi (French)
Uriel Orlow - Unmade Film, Al-Ma'mal Foundation for Contemporary Art, Centre culturel suisse, Les Complices, John Hansard Gallery, Jerusalem, Paris, Zurich, Southampton, 9 April - 26 April 2013, 3 May - 14 July 2013, 15 May - 8 June 2013, 24 February - 18 April 2015
boek
Keywords: Orlow, Uriel